2017
DOI: 10.1177/0260106017704798
|View full text |Cite
|
Sign up to set email alerts
|

Household food insecurity among people living with HIV in Sagamu, Nigeria: A preliminary study

Abstract: The prevalence of household food insecurity in this study was high. Living conditions were significantly associated with food insecurity. Socio-economic conditions need to be improved, to optimize the health and food security status of people living with HIV in Sagamu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 19 publications
4
18
2
Order By: Relevance
“…This finding is lower than the finding of the study conducted in Senegal (84.6%) [30], Uganda (78.5%) [31], Nigeria (71.7%) [32] and one of global systematic review (71%) of food insecurity role on treatment Adherence [33]. As indicated above, the difference may be due to food insecurity measurement difference, difference in sample size, difference in the socio-demographic and economic status of the included population in the analysis.…”
Section: Discussioncontrasting
confidence: 73%
“…This finding is lower than the finding of the study conducted in Senegal (84.6%) [30], Uganda (78.5%) [31], Nigeria (71.7%) [32] and one of global systematic review (71%) of food insecurity role on treatment Adherence [33]. As indicated above, the difference may be due to food insecurity measurement difference, difference in sample size, difference in the socio-demographic and economic status of the included population in the analysis.…”
Section: Discussioncontrasting
confidence: 73%
“…This finding is similar to the findings of other studies reported from different countries in Sub-Saharan Africa. For example, food insecurity was reported as 19.4% in Tanzania (Kabalimu et al, 2018), 67% in Namibia (Hong et al, 2014), 71.7% in Nigeria (Sholeye et al, 2017), and 35.2% in Central Ethiopia (Gebremichael et al, 2018). Hence, such higher prevalence of food insecurity among PLHIV continues affecting the health and development of the region (Laar et al, 2015; United Nations Programme on HIV and AIDS, 2014), affects treatment outcome (Yacobson et al, 2016; Young et al, 2014), and quality of life (Palermo et al, 2013; Ivers and Cullen, 2011; Tsai et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In Uruguay and Brazil, household income strongly correlated with food insecurity [30,31]. Among people living with HIV in Nigeria, food insecurity was associated with educational attainment, occupation, and living conditions such as housing and property ownership status [32]. Social structures also play a major role in food insecurity.…”
Section: Introductionmentioning
confidence: 99%